“FUND” LENDING AS AN EFFECTIVE TOOL OF STATE SUPPORT FOR FARMERS - A. V. Tikhonova (Финансы: теория и практика, 2018)
The article is devoted to the topical problem of the development of agro-industrial complex, in particular, the development of the novelty model of agricultural lending. Experience of crediting of agriculture inRussiasince 1992 till now is considered. We provide a critical approach to the assessment of the current system of agricultural credit, which requires the presence of another economic incentive — the budget subsidy.Our purpose was a comprehensive author’s study of the problems of applying the practice of preferential agricultural lending, as well as the development of proposals aimed at improving the system of state support for the agricultural credit system.The methodological tools of the research include comparative methods of analysis, as well as analytical methods of cognition.We carried out the analysis of the models of crediting of farmers applied for the specified period and the main problems in practice of their application. As the most effective model of farmer’s lending defined “fund” model, used from 1997 to 2001. The main drawback of this system is the fragmentation of property interest in the subject of agriculture in a single loan obligation. The author developed a new system of agricultural lending, based on the “fond” model of the 90s. Its distinctive feature is dual targeting — for in economic entities (small and large businesses) and credit institutions (banks and credit cooperatives), while at the same time with maintaining a high level of state control (which is provided by a single source of credit resources — the state).The results of the study can be used in the development of both individual credit measures of state support for agricultural producers, and in the preparation of the State program of development of agriculture and regulation of markets of agricultural products, raw materials and food.